Association of diabetes treatment with long‐term glycemic patterns in patients with type 2 diabetes mellitus: A prospective cohort study. Issue 4 (10th January 2019) - Luo, Miyang; Tan, Chuen Seng; Lim, Wei Yen; Chia, Kee Seng; Tang, Wern Ee; Tai, E. Shyong; Venkataraman, Kavita
Abstract: Aim: This study aimed to analyze diabetes treatment and treatment changes in association with long‐term glycemic patterns in an Asian population with diabetes. Materials and methods: This was a prospective cohort study of 6218 patients with type 2 diabetes managed in public primary care clinics in Singapore. Clinical data from 2011 to 2016 were extracted from electronic medical records, including serial HbA1c measurements and dispensed antidiabetic medication records. Patterns of longitudinal HbA1c trajectories were identified using latent class growth analysis, and patients' annual treatment plans were compared between subgroups with different HbA1c patterns. Results: We identified four distinct HbA1c patterns. Eighty‐one percent of patients were classified in the low‐stable group, where monotherapy and dual therapy with oral agents were the most common treatments. We also identified three groups with poorer control, with moderate‐stable (14%), moderate‐increase (3%), and high‐decrease (2%) HbA1c patterns. Insulin treatment was most prevalent in these groups, with 61% to 72% of subjects receiving insulin treatment in 2016. More than 60% of subjects in poorer control groups had experienced treatment intensification during follow‐up. Addition of multiple insulin injections was the most common intensification in moderate‐increase and high‐decrease groups. Conclusions: Treatment reflected and was appropriate to the extent of dysglycemia in this population. A small group of patients had deteriorating glycemic control, in spite of being treated with multiple insulin injections, suggesting non‐response or non‐adherence to treatment. Further investigation is needed to identify reasons for the deteriorating control observed and design effective interventions for these patients.